Fatigue in AISI 4340 steel thermal spray coating by HVOF for aeronautic application - Bonora, R. G. [UNESP] (2010)
Currently, high-strength materials, particularly AISI 4340 steel, are used in several landing gear components. Due to the high resistance to wear and corrosion required, the components are usually coating by hard chromium. This treatment produces waste, such as Cr+ 6 (hexavalent chromium), generally after applying the coating of hard chromium which is harmful to health and the environment. The process HVOF (High-velocity-oxygen-fuel) is considered a promising technique for deposition of hard chromium alternative coatings, for example, coatings based on tungsten carbide. This technique provides high hardness and good wear strength and more resistance to fatigue when compared to AISI 4340 hard chromium coated. To minimize loss fatigue due to the process of deposition, shot peening is used to obtain a compressive residual stress. The aim of this study was to analyze the effects of the tungsten carbide thermal spray coating applied by the HVOF, in comparison to the conventional hard chromium electroplating on the AISI 4340 high strength steel behavior in fatigue. Optical microscopy and scanning electron microscopy were used to observe crack origin sites, thickness and adhesion of the coating. (C) 2010 Published by Elsevier Ltd.